2021
DOI: 10.52403/ijhsr.20210714
|View full text |Cite
|
Sign up to set email alerts
|

Serosurveillance of Anti SARS-Cov-2 Antibodies among Essential Workers in Navi Mumbai - A Single Centre Study

Abstract: Background – COVID – 19 is the latest raging pandemic that the world is facing at the moment. Frontline workers have been highly exposed to this disease and majority of them have suffered from this deadly disease too. Studying the prevalence of antibodies among frontline workers in different areas is crucial for understanding the potential risk of transmission, the prevalence of herd immunity, vaccine deployment and risk stratification in different areas of work. Materials and Methods – A prospective study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Tripathi et al (2020) reported that HCWs were more educated with regard to the COVID-19 symptoms, incubation time, problems in high-risk patients, and had greater access to therapy than other residents (non HCWs) [ 39 ]. In Navi Mumbai in May 2021, serosurveillance of anti-SARS-CoV-2 antibodies among essential workers revealed that police personnel had a 72% seropositivity rate, whereas HCWs had a 48% positivity rate [ 40 ]. Moreover, we observed that, among the garment workers, just under 20% received vaccines and just above 50% were seropositive, which might have majorly been achieved from natural infections ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tripathi et al (2020) reported that HCWs were more educated with regard to the COVID-19 symptoms, incubation time, problems in high-risk patients, and had greater access to therapy than other residents (non HCWs) [ 39 ]. In Navi Mumbai in May 2021, serosurveillance of anti-SARS-CoV-2 antibodies among essential workers revealed that police personnel had a 72% seropositivity rate, whereas HCWs had a 48% positivity rate [ 40 ]. Moreover, we observed that, among the garment workers, just under 20% received vaccines and just above 50% were seropositive, which might have majorly been achieved from natural infections ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…HCWs had a 48% positivity rate [40]. Moreover, we observed that, among the garment workers, just under 20% received vaccines and just above 50% were seropositive, which might have majorly been achieved from natural infections (Figure 1).…”
Section: Discussionmentioning
confidence: 84%
“…Tripathi et al, 2020 reported that HCWs were more educated of COVID-19 symptoms, incubation time, problems in high-risk patients, and had greater access to therapy than other residents (non HCWs) [ 39 ]. In Navi Mumbai in May 2021, serosurveillance of anti-SARS-Cov-2 antibodies among essential workers revealed that police personnel had a 72% seropositivity rate, whereas HCWs had a 48% positivity rate [ 40 ]. Moreover, we observed that, among the garment workers, just under 20% received vaccines and just above 50% were seropositive, which might have majorly been achieved from natural infections ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%